Effect of soil covers on coal waste dumps in KwaZulu-Natal on abiotic factors and bacteria causing acid mine drainage - Cleghorn, Charles, 1970- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1997.